Daughters' Inheritance Rights: Indonesian Legal Paradigms, Human Rights, and a Comparative Analysis with India and Pakistan - Maftuha Kiswah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2026)
This article examines daughters’ inheritance rights from a human rights perspective in Indonesia through a comparative analysis with India and Pakistan. Indonesia’s inheritance law is shaped by legal pluralism, consisting of Western Civil Law, Islamic Law under the Compilation of Islamic Law, and diverse customary laws. Using a normative juridical method with a Human Rights-Based Approach (HRBA) and case-law analysis, this article evaluates how legal reforms, judicial decisions, and interpretive developments affect women’s substantive inheritance rights in the three jurisdictions. The findings show that legal reform without cultural transformation, as seen in India’s Hindu Succession (Amendment) Act 2005, may produce unintended consequences, including increased sex-selective abortion and female infant mortality. In contrast, Indonesia’s gradual jurisprudential development, reflected in Supreme Court Decision No. 179 K/SIP/1961 and progressive interpretations of maqāṣid al-sharīʿah, demonstrates that legal pluralism can be harmonized with international human rights standards. Pakistan’s experience further illustrates strong customary resistance to formal legal guarantees. This article concludes that integrating CEDAW standards with context-sensitive religious and customary interpretations offers a viable path toward substantive gender equality in inheritance law